Prevalence and characterization of Salmonella enterica serovar in retail meats in market place in Uighur, Xinjiang, China. (June 2016) - Yin, Mingyuan; Yang, Baowei; Wu, Yun; Wang, Lu; Wu, Haotian; Zhang, Tao; Tuohetaribayi, Gulinazi
Abstract: Ninety nine Salmonella isolates recovered from 1414 retail meats were characterized by serotyping, antimicrobial susceptibility, pulsed-field gel electrophoresis (PFGE), presence of amino acid mutation in quinolone resistance determination region (QRDR) of DNA gyrase subunit A (GyrA) and topoisomerase IV subunit C (ParC), and of qnr A, qnr B, qnr S, aac(6′)-Ib, qep A, and oqx AB. Among 1414 retail meat samples, 96 (6.8%) including 49 (9.0%) chickens, 22(6.8%) lambs, 10 (4.8%) beefs, 13 (6.8%) porks and 2(1.4%) horse meats were positive to Salmonella . The commonly detected Salmonella serotypes were S . Hadar (n = 21, 21.2%), S . Enteritidis (n = 17, 17.2%), S . London (n = 17, 17.2%), and S . Havana (n = 11, 11.1%). Eighty four (84.8%) isolates were simultaneously resistant to more than three antimicrobial agents. Antibiotic resistance was most commonly found to trimethoprim (100%), and a less extent to chloramphenicol (88.9%), tetracycline (63.6%), nalidixic acid (58.6%), sulfisoxazole (57.6%), streptomycin (43.4%), trimethoprim/tulfisoxazole (41.4%), ampicillin (25.6%), amoxicillin/clavulanate (25.6%), kanamycin (6.1%), ceftriaxone (5.1%), gentamicin (3.0%), cefoxitin (2.0%), and amikacin (1.0%). qnr A (11.1%), qnr B (34.3%), qnr S (8.1%), aac(6′)-Ib (7.1%), qep A (7.1%), oqx A (10.1%) and oqx B (9.1%) were detected from the 99 isolates. Amino acid substitutions of Asp87Asn (4.8%), Asp87Tyr (28.6%), Asp87Val (4.8%), Ser83Phe (52.4%), Ser83Tyr (7.1%) and Gly75Phe (2.4%) in GyrA were detected, as well as Thr57Ser (98.6%) and Gly53Val (1.4%) in ParC. Mutations of Ser83Phe (GyrA)/Thr57Ser (ParC) that simultaneously detected in GyrA and ParC were found in 22 isolates. Totally 82 different DNA patterns generated after the 99 isolates were subtyped using PFGE. The results demonstrated that the prevalence of Salmonella in retail meats in Uighur of Xinjiang province were not common, however, the isolates exhibited multidrug resistance, phenotypical and genotypical diverse. Highlights: 96 of 1414 retail meats in Uighur, Xinjiang, China were positive for Salmonella . 18 serotypes were identified, S . Hadar, S . Enteritidis, S . London, and S . Havana were most prevalent. 82 DNA profiles generated after 99 isolates were subtyped by PFGE. Multidrug resistance was found among the 99 Salmonella isolates. Mutations in GyrA and ParC, and qnr A, qnr B, qnr S, aac(6′)-Ib, qep A, and oqx AB in Salmonella isolates were detected.